Economic and political consequences of the compulsory voting in public parliamentary elections: Czech case study - Ondrej Kuba; Jan Stejskal (Economies, 2021)
Scholars who study compulsory voting realize their research in countries where compulsory voting already exists. On the contrary, there are not many studies that deal with ex ante analyses of the economic and political consequences of voter behavior caused by a new element in public elections-compulsory voting. Therefore, the aim of this paper is to find out what voters' reactions will cause when compulsory voting is introduced in the Czech Republic. This paper has the ambition to contribute to the understanding of the economic and political context of sanctions for non-voters. The analysis of non-voters' willingness to change their behavior due to the fine and the determination of the amount of this fine in the Czech Republic are the practical benefits of this study. In this way, we determine the "abstention price" of a vote. The input data of the analysis are data obtained by a questionnaire survey conducted in the Czech Republic in 2020; the target group is 807 respondents. The basic statistical operations, and binary and multinomial logistic regressions were employed in this study. The results of the research show that compulsory voting has only a minimal effect on the turnout. The introduction of compulsory voting changes the characteristics of the typical voter. Voters with lower political interest and political knowledge will take part in the elections more often. The fine that non-voters would be willing to pay is approx. 6% of their average monthly income.
Keywords: 330; case study; compulsory participation; Czech Republic; economic and political consequences; public elections